Analysis of the discrepancies identified during medication reconciliation on patient admission in cardiology units: a descriptive study - Natália Fracaro Lombardi; Antonio Eduardo Matoso Mendes; Rosa Camila Lucchetta; Wálleri Christini Torelli Reis; Maria Luiza Drechsel Fávero; Cassyano Januário Correr
ABSTRACT Objectives: this observational study aimed to describe the discrepancies identified during medication reconciliation on patient admission to cardiology units in a large hospital. Methods: the medication history of patients was collected within 48 hours after admission, and intentional and unintentional discrepancies were classified as omission, duplication, dose, frequency, timing, and route of drug administration. Results: most of the patients evaluated were women (58.0%) with a mean age of 59 years, and 75.5% of the patients had a Charlson comorbidity index score between 1 and 3. Of the 117 discrepancies found, 50.4% were unintentional. Of these, 61.0% involved omission, 18.6% involved dosage, 18.6% involved timing, and 1.7% involved the route of drug administration. Conclusion: this study revealed a high prevalence of discrepancies, most of which were related to omissions, and 50% were unintentional. These results reveal the number of drugs that are not reincorporated into the treatment of patients, which can have important clinical consequences.